THE EFFECT OF THE USE OF BIG BOOK MEDIA ON THE INITIAL READING ABILITY OF GRADE 1 STUDENTS SDN SITIMULYO 01 PATI - Muhammad Mansur; Ervina Eka Subekti; Kartinah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine the influence of the use of Big Book media on the initial reading ability of grade I students of SDN Sitimulyo 01 Pati. This study uses a quantitative approach with a pre-experimental design through a one-group pretest–posttest model. The subject of the study is a grade I student of SDN Sitimulyo 01 Pati. The data collection technique was carried out through initial reading ability tests before and after treatment. The data obtained was analyzed using the help of the SPSS program, including descriptive statistical analysis, normality test, and Paired Sample t-Test. The results of the study showed that there was an increase in students' initial reading ability after using Big Book media. The average score of students' initial reading ability increased from 51.92 in the pretest to 88.46 in the posttest. The results of the hypothesis test showed a significance value of 0.001 (p < 0.05), so it can be concluded that there is a significant influence of the use of Big Book media on students' initial reading ability. Based on the results of the study, it can be concluded that Big Book media is effectively used as a learning medium to improve the initial reading ability of elementary school students. Keywords: Big Book media, reading beginnings, elementary school